A Dilemma between Firm Survivability and Business Ethic in Indonesia - Kuncoro, Ari (Komisi Pemberantasan Korupsi, 2018)
in the 1998 economic crisis, the public perception on corruption in Indonesia was changed almost overnight in 1998. After almost 30 years of recognizing corruption as economically benign or even beneficial to the economic development, the public opinion was now shifting toward a concern that corruption hampered economic development (MacIntyre [2001]). What has been happening with small corruption at the firm level is however relatively unknown. For a private firm the primary concern of stakeholders from management, employees and shareholders is sustainability. Business environment however is not always friendly. Uncertainty could come from changes in government regulations. Facing the possibility of business stoppage, business ethics and illegality may have little meaning, many firms would have no choice but to pay grease money to speed up the process provided that the amount is Ã¢â‚¬Å“small.Ã¢â‚¬Â